Isomorfisme dan Peran Kepolisian Masyarakat di Indonesia dan Selandia Baru - Seala Syah Alam; Sudarsono Hardjosoekarto; Arthur Josias Simon Runturambi; Chairul Muriman Setyabudi (Magister of Law, Faculty of Law, University of Mataram, 2026)
Community policing has become a strategic approach adopted in many countries to enhance public trust in the police and to create safer and orderly neighborhoods. It emphasizes active partnership between the police and the public in detecting, preventing, and tackling crime collaboratively. Indonesia and New Zealand have both implemented community policing systems with characteristics that reflect institutional isomorphism. This study examines isomorphism in community policing in the two countries and explore the development of community policing practices through a literature case study. Data were obtained through digital research, interviews, observations, and documentation, which were analyzed using textual and social network analysis methods. The findings reveal significant similarities between policing systems of the two countries’, including the existence of a single national police force that respects the principle of independence and the adoption of community policing models. Nevertheless, differences remain, mainly due to each country’s distinct social, cultural, and historical contexts. These variations influence the implementation patterns of community policing, although both countries share similar core objectives, namely, improving security and building public trust. Thus, the findings suggest that isomorphism in policing provides opportunities for sharing best practices across countries, enabling international collaboration and mutual learning to improve the effectiveness of community policing strategies.